Hard-word dictionaries in 17th-Century England: analysing prefaces and entries - Domínguez Rodríguez, María Victoria (Cuadernos para la Docencia, 2013)
The present workbook consists in a selection of prefaces and vocabulary entries from four 17thcentury hard-word dictionaries, which includes the first three acknowledged dictionaries published in England and a fourth representative from the second half of the century; namely: An English Dictionary (1676). The methodological approach followed in each unit consists in three steps: (i) introduction of some preliminary remarks for contextualization purposes, alongside short-format references for further reading: (ii) comprehensive reading of the preface to grasp its main ideas and be able to answer some related questions and commenting on specific EModE linguistic features; and (iii) critical analysis of certain vocabulary entries.